Preparation of Catalyst and its Application in Thermal and Photo Vapor Phase Oxidation Compounds - Tiama, Abeer Adeem; Kadhum, Mousa Umran (Al-Qadisiyah Journal of Pure Science, 2017)
catalyst was prepared from mixture ; Fe2O3-Cr2O3 by loading method in different ratios (0:2,0.5:1.5,1:1,1.5:0.5 and 2:0) and supported on granulated kaolin clay with different . The thermal vacuum evaporation technique was at temperature 323K .Characteristic catalyst was prepared by X-Ray diffraction.and studied some physical properties for catalyst such as Surface area , particles size, porosity , pores size (Mesh No.), density and electricalconductivity . Also studied the activity of prepared catalyst by thermal and photo oxidation for 2-brobanol at298 - 493K